N-heterocyclic iminium ions catalyzed Friedel–Crafts type alkenylation of arenes with alkynes: A metal free and solvent free approach - Preethi Raja; Tapas Ghatak (Catalysis Communications, 2023)
The current manuscript elucidates a pioneering approach for achieving regioselective Markovnikov-type hydroarylation of alkynes, without the use of any metal catalysts. The aforementioned process is expedited through the implementation of 2-amino-perimidinium bromide and TFA as catalyst systems and is executed in the absence of solvents, thereby expanding the range of substrates (including arenes and alkynes). The correlation between the stoichiometric reactions and experimental data substantiates the postulated reaction mechanism.